Cateterismo intermitente limpo: método de ensino para cuidadores de crianças com disfunção vésico-esfincteriana - Martins, Gisele (2004)
The purpose of this research was to develop, apply and evaluate a teaching method of systematization for the clean intermittent catheterization (C.I.C.) technique for caregivers of children suffering from neurogenic bladder dysfunction. This is a descriptive study, carried out starting from the elaboration of an educative manual specifically produced for this purpose. A total of 23 caregivers and their children were investigated and the following principal results were obtained: 22 of the caregivers were mothers of the children with the disorder and were their principal or unique caregiver; all the children suffered myelomeningocele as the cause of the neurogenic bladder dysfunction and there was no predominance of either gender. The majority of the caregivers understood reasonably well the significance of neurogenic bladder dysfunction and the importance of the C.I.C. They followed the proposed technique of the procedure, observed an improvement in the child s health and reported that the manual was very important and adequate. The planning of the teaching method of C.I.C. proposed in this research, proved to be effective in regards to health education, as was confirmed in the evaluation of caregivers in respect to the cognitive, psychomotor and emotional aspects. Moreover, the role of nurses as educators in this field must be stressed, since they provide essential qualified assistance to caregivers and children with neurogenic bladder dysfunction.